PENGARUH KUALITAS PRODUK TERHADAP BRAND IMAGE DAN DAMPAKNYA TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK ALDO SHOES - Cindy Oktavia Cahayani; Sutar Sutar (STIE Muhammadiyah Jakarta, 2020)
This study aims to analyze empirical evidence of the effect of product quality on brand image and its impact on purchasing decisions on Aldo Shoes products at Mall Kelapa Gading 2 North Jakarta. Samples obtained as many as 90 respondents, sampling techniques using non-probability sampling, namely sampling techniques that provide equal opportunities for each element (member) of the population to be selected as sample members. Analysis of the data used is Structural Equation Modeling (SEM).The results of this study indicate that product quality on brand image has a positive and significant effect, so that if the quality of the product gets better the brand image will increase. Product quality on purchasing decisions has a positive and significant effect, so that if the quality of the product gets better the purchasing decision will increase. Brand image of purchasing decisions has a positive and significant effect, so that if the brand image of the product is increasingly attached to the minds of consumers, purchasing decisions will increase. And product quality on purchasing decisions through brand image has positive and significant influence.